Why are Prices Sticky? Evidence from Business Survey Data - Heike Schenkelberg (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2011)
This paper offers new insights on the price setting behaviour of German retail firms using a novel dataset that consists of a large panel of monthly business surveys from 1991-2006. The firm-level data allows matching changes in firms' prices to several other firm-characteristics. Moreover, information on price expectations allow analyzing the determinants of price updating. Using univariate and bivariate ordered probit specifications, empirical menu cost models are estimated relating the probability of price adjustment and price updating, respectively, to both time- and state- dependent variables. First, results suggest an important role for state-dependence; changes in the macroeconomic and institutional environment as well as firm-specific factors are significantly related to the timing of price adjustment. These findings imply that price setting models should endogenize the timing of price adjustment in order to generate realistic predictions concerning the transmission of monetary policy. Second, an analysis of price expectations yields similar results providing evidence in favour of state-dependent sticky plan models. Third, intermediate input cost changes are among the most important determinants of price adjustment suggesting that pricing models should explicitly incorporate price setting at different production stages. However, the results show that adjustment to input cost changes takes time indicating "additional stickiness" at the last stage of processing.
urn:nbn:de:bvb:19-epub-12158-2
Keywords: E31; E32; E50; 330; Price setting behaviour; time dependent pricing; state dependent pricing; sticky prices; Einzelhandelspreispolitik; Preisrigidität; Preismanagement; Zeit; Anpassungskosten; Schätzung; Konjunkturumfrage; Deutschland